Use of the Behavior Assessment Tool in 18 Pilot Residency Programs. Issue 4 (October 2020) - Armstrong, April D.; Agel, Julie; Beal, Matthew D.; Bednar, Michael S.; Caird, Michelle S.; Carpenter, James E.; Guthrie, Stuart T.; Juliano, Paul; Karam, Matthew; LaPorte, Dawn; Marsh, J. Lawrence; Patt, Joshua C.; et al.
Abstract : Background: The purpose of this study was to determine the feasibility and evaluate the effectiveness of the American Board of Orthopaedic Surgery Behavior Tool (ABOSBT) for measuring professionalism. Methods: Through collaboration between the American Board of Orthopaedic Surgery and American Orthopaedic Association's Council of Residency Directors, 18 residency programs piloted the use of the ABOSBT. Residents requested assessments from faculty at the end of their clinical rotations, and a 360° request was performed near the end of the academic year. Program Directors (PDs) rated individual resident professionalism (based on historical observation) at the outset of the study, for comparison to the ABOSBT results. Results: Nine thousand eight hundred ninety-two evaluations were completed using the ABOSBT for 449 different residents by 1, 012 evaluators. 97.6% of all evaluations were scored level 4 or 5 (high levels of professional behavior) across all of the 5 domains. In total, 2.4% of all evaluations scored level 3 or below reflecting poorer performance. Of 431 residents, the ABOSBT identified 26 of 32 residents who were low performers (2 or more < level 3 scores in a domain) and who also scored "below expectations" by the PD at the start of the pilot project (81% sensitivity and 57% specificity), including 13 of these residents scoring poorly in all 5 domains. Evaluators found the ABOSBT was easy to use (96%) and that it was an effective tool to assess resident professional behavior (81%). Conclusions: The ABOSBT was able to identify 2.4% low score evaluations (<level 3) for all residents. The tool was concordant with the PD for 81% of the residents considered low performers or "outliers" for professional behavior. The 5-domain construct makes it an effective actionable tool that can be used to help develop performance improvement plans for residents. Level of Evidence: Level II